Kesehatan Masyarakat Sebagai Pilar Peningkatan Kualitas Hidup - Harlina Harlina; Rezqiqah Aulia Rahmat (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Public health plays a strategic role in improving the quality of life of individuals and communities as a whole. The public health approach focuses not only on disease treatment but also on promotive and preventive efforts through community empowerment, environmental improvement, and control of health risk factors. This study aims to examine the role of public health as a key pillar in improving quality of life. The research method used is a descriptive study with a qualitative approach through a literature review and health policy analysis. The results of the study indicate that planned and sustainable public health interventions can improve the health, productivity, and social welfare of communities. The study concludes that public health is an important foundation for sustainable development and improving quality of life.